Antioxidant and ACE-inhibitory activities of hemp (Cannabis sativa L.) protein hydrolysates produced by the proteases AFP, HT, Pro-G, actinidin and zingibain. (15th July 2016) - Teh, Sue-Siang; Bekhit, Alaa El-Din A.; Carne, Alan; Birch, John
Highlights: Enzymatic hydrolysis of HPIs produced antioxidative and ACE-inhibitory peptides. HT had the highest caseinolytic activity. Higher proteolytic activity led to the lower H o and zeta potential. HT resulted in the highest bioactivities of HPHs in 2 h among all proteases. Al-HPI was the better substrate than AC-HPI that led to the higher bioactivities. Abstract: Hemp protein isolates (HPIs) were hydrolysed by proteases (AFP, HT, ProG, actinidin and zingibain). The enzymatic hydrolysis of HPIs was evaluated through the degree of hydrolysis and SDS-PAGE profiles. The bioactive properties of the resultant hydrolysates (HPHs) were accessed through ORAC, DPPḢ scavenging and ACE-inhibitory activities. The physical properties of the resultant HPHs were evaluated for their particle sizes, zeta potential and surface hydrophobicity. HT had the highest rate of caseinolytic activity at the lowest concentration (0.1 mg mL −1 ) compared to other proteases that required concentration of 100 mg mL −1 to achieve their maximum rate of caseinolytic activity. This led to the highest degree of hydrolysis of HPIs by HT in the SDS-PAGE profiles. Among all proteases and substrates, HT resulted in the highest bioactivities (ORAC, DPPḢ scavenging and ACE-inhibitory activities) generated from alkali extracted HPI in the shortest time (2 h) compared to the other protease preparations.